EGALITERIANISME DALAM HINDU - Ananda, I Nyoman (WIDYA DUTA, 2012)
Religion is a social phenomenon that contains various interests. Therefore sacred texts have been interpreted continually and contextually. Any efforts to standardize the interpretation to be absolute will cause a lot of problems one of the is unegalitarianism. It has also been occurred in Hinduism both in India and in Bali causing caste problems. The role of liberation theology is essential to free mankind from the bondage of unegalitarianism and restore the position of religion as the human liberator. Key Words: Egaliterianism, Hinduism, Liberation Theology.